The existence of Hall polynomials for x2-bounded invariant subspaces of nilpotent linear operators - Kasjan, Stanisław; Kosakowska, Justyna (Journal of pure and applied algebra, 2022)
We prove the existence of Hall polynomials for x2-bounded invariant subspaces of nilpotent linear operators.